Endoplasmic reticulum stress in pancreatic β-cell dysfunctionality and diabetes mellitus: a promising target for generation of functional hPSC-derived β-cells in vitro - Diane, Abdoulaye; Allouch, Asma; Mu-U-Min, Razik Bin Abdul; Al-Siddiqi, Heba Hussain (Frontiers in Endocrinology, 2024)
Diabetes mellitus (DM), is a chronic disorder characterized by impaired glucose homeostasis that results from the loss or dysfunction of pancreatic β-cells leading to type 1 diabetes (T1DM) and type 2 diabetes (T2DM), respectively. Pancreatic β-cells rely to a great degree on their endoplasmic reticulum (ER) to overcome the increased secretary need for insulin biosynthesis and secretion in response to nutrient demand to maintain glucose homeostasis in the body. As a result, β-cells are potentially under ER stress following nutrient levels rise in the circulation for a proper pro-insulin folding mediated by the unfolded protein response (UPR), underscoring the importance of this process to maintain ER homeostasis for normal β-cell function. However, excessive or prolonged increased influx of nascent proinsulin into the ER lumen can exceed the ER capacity leading to pancreatic β-cells ER stress and subsequently to β-cell dysfunction. In mammalian cells, such as β-cells, the ER stress response is primarily regulated by three canonical ER-resident transmembrane proteins: ATF6, IRE1, and PERK/PEK. Each of these proteins generates a transcription factor (ATF4, XBP1s, and ATF6, respectively), which in turn activates the transcription of ER stress-inducible genes. An increasing number of evidence suggests that unresolved or dysregulated ER stress signaling pathways play a pivotal role in β-cell failure leading to insulin secretion defect and diabetes. In this article we first highlight and summarize recent insights on the role of ER stress and its associated signaling mechanisms on β-cell function and diabetes and second how the ER stress pathways could be targeted in vitro during direct differentiation protocols for generation of hPSC-derived pancreatic β-cells to faithfully phenocopy all features of bona fide human β-cells for diabetes therapy or drug screening.